PELANGGARAN MAKSIM PRINSIP KERJASAMA DAN MAKSIM PRINSIP KESOPANAN DALAM DRAMA SERI HOUSE M.D.: SUATU TELAAH SOSIOPRAGMATIK - , Wahyu Adri Wirawati, Prof. Dr. Soepomo Poedjosoedarmo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study, entitled \"Violations Of The Cooperative Principles Maxims And The Politeness Principles Maxims In The Drama Series House M.D.: A Study On Sociopragmatics\", analyzes doctor Gregory Houseâs utterances. The aims of this study are to describe violations of the cooperative principles maxims and the politeness principles maxims in the drama series, to describe implicatures which occur as a result of the violations on both principles, and describes the social aspects that affect Gregory Houseâs utterances. This research is a qualitative descriptive study. The data were obtained from DVD of drama series House MD, season eight, episode two to seven. The data were obtained by using observation method and analyzed by using pragmatic identity method. The results of data analysis are presented informally and formally. After analyzing the data, the violations of maxim of quantity, maxim of quality, maxim of relation and maxim of manner of the cooperative principles can be found in all episodes, and violation of maxim of quality is the most commonly found in the data. Violation of politeness principles maxims also can be found in all episodes, namely violation of tact maxim, maxim of generosity, maxim of approbation, maxim of modesty, maxim of agreement, and maxim of sympathy. Violation of maxim of generosity is the most commonly found in the data. The implicatures that can be found from the violations of the cooperative principles are insulting, providing explanation, ordering, rejecting, accusing, asking for attention, making fun the others, and threatening. Whereas, implicatures that can be found from the violations of the politeness principles are ordering, insulting, rejecting, prohibiting, bragging, showing indifference, and showing dissatisfaction. Social aspects that affect Houseâs speeches are analyzed based on Hymesâs SPEAKING theory. Most of the conversations take place in the hospital that lead to the using of medical terms related to the patient's condition. Social aspects, such as aspects of age, gender aspects, aspects of the social level, and the aspects of ethnicity, are not ignored by House. Several purposes in House speechs are often giving an explanation, obtaining something, insulting, and ordering. House often uses a casual tone of voice.